Competitive Landscape Shifts: The Influence of Strategic Entrepreneurship on Shifts in Market Commonality - Withers, Michael C.; Ireland, R. Duane; Miller, Danny; Harrison, Joseph S.; Boss, David S. (Academy of Management Review, 2018)
The competitive dynamics literature offers important insights regarding competitive behavior; however, the critical question of how previously nonrival firms become more direct competitors remains unanswered. To address this question, we extend the strategic entrepreneurship construct to develop a theory-based model of competitive landscape shifts. We theorize that firms engaging in strategic entrepreneurship will be better able to recognize entrepreneurial opportunities outside of their competitive domain(s), which will enable them to enact radical competitive actions. In turn, radical competitive actions will lead to shifts where these firms increase their market commonality with competitors with dissimilar resources and/or decrease their market commonality with competitors with similar resources. In developing our model of competitive landscape shifts, we also consider several important boundary conditions that influence the proposed relationships.